Metabolic Alterations in Preneoplastic Development Revealed by Untargeted Metabolomic Analysis - Myllymäki, Henna; Astorga Johansson, Jeanette; Grados Porro, Estefania; Elliot, Abigail; Moses, Tessa; Feng, Yi (Frontiers in Cell and Developmental Biology, 2021)
Metabolic rewiring is a critical hallmark of tumourigenesis and is essential for the development of cancer. Although many key features of metabolic alteration that are crucial for tumour cell survival, proliferation and progression have been identified, these are obtained from studies with established tumours and cancer cell lines. However, information on the essential metabolic changes that occur during pre-neoplastic cell (PNC) development that enables its progression to full blown tumour is still lacking. Here, we present an untargeted metabolomics analysis of human oncogene hRASG12V induced PNC development, using a transgenic inducible zebrafish larval skin development model. By comparison with normal sibling controls, we identified six metabolic pathways that are significantly altered during PNC development in the skin. Amongst these altered pathways are pyrimidine, purine and amino acid metabolism that are common to the cancer metabolic changes that support rapid cell proliferation and growth. Our data also suggest alterations in post transcriptional modification of RNAs that might play a role in PNC development. Our study provides a proof of principle work flow for identifying metabolic alterations during PNC development driven by an oncogenic mutation. In the future, this approach could be combined with transcriptomic or proteomic approaches to establish the detailed interaction between signaling networks and cellular metabolic pathways that occur at the onset of tumour progression.